Score for the Survival Probability of Patients With Orbital Rhabdomyosarcoma After Surgery: A Long-Term and Large Cohort Study - Zhang, Yu; He, Chaobin; Lian, Yu; Xiao, Huiming (Frontiers in Oncology, 2020)
Orbital rhabdomyosarcoma (RMS) is a relatively rare primary malignancy occurring in children. The objective of this study was to evaluate the cumulative incidence of cancer-specific death and competing risk of death among RMS patients after surgery and to build nomograms to predict overall survival (OS) and cancer-specific survival (CSS) based on a large population-based cohort. The records of 217 patients who were pathologically diagnosed with an orbital RMS between 1973 and 2015 from the Surveillance, Epidemiology, and End Results (SEER) database were retrospectively analyzed. The 10-, 20- and 40-year OS rates and cancer-specific mortality were 82.5%, 72.2%, and 48.9%, respectively and 14.8%, 21.7%, and 21.7%, respectively. The established nomograms were well calibrated and validated, with a concordance index (C-index) of 0.901 and 0.944 for OS prediction, 0.923 and 0.904, for CSS prediction in the training and validation cohorts, respectively. The values of area under the receiver operating characteristic curve (AUC) for 10-, 20-, and 40-year OS and CSS prediction were 0.908, 0.826, and 0.847, and 0.924, 0.863, and 0.863, respectively. The established nomogram showed relatively good performances and could be convenient individualized predictive tools for prognostic prediction in RMS patients.